HUBUNGAN ANTARA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI DENGAN KINERJA BAWAHAN DI SEKOLAH MENENGAH KEJURUAN (SMK) PELITA NUSANTARA 1 SEMARANG - Tri Joko Utomo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
The SMK Pelita Nusantara 1 Semarang’s effort to realize their vision and mission is a very hard duty, that needs good performance from all of component itself. Performance is good work or output of work that is produced by employee’s capacity and wish for produce output that matchwith plans or standards of work to be defined. Many factors that influenced performance such as leadership and communication. The purpose of this study is to describe and to analize the relationship between : (1) Tranformational leadership with performance of employees at SMK Pelita Nusantara 1 Semarang; (2) Communication with performance of employees at SMK Pelita Nusantara 1 Semarang; and (3) Tranformational leadership and communication with performance of employees at SMK Pelita Nusantara 1 Semarang. Population in this study is the 40 teachers of SMK Pelita Nusantara 1 Semarang. Because it’s small population, so used total sampling or sensus research. Tool of analisys that is used to get research’s goals is inferential analysis (correlation Rank kendall Tau b and Rank Kendall W).The research’s resultant prove that : (1) Coefisien of correlation between tranformational leadership with performance of employees 0,301; (2) Coefisien of correlation between communication with performance of employees 0,303; and (3) Coefisien of correlation between tranformational leadership and communication with performance of employees 0,780.